Exploring the link between estimated glucose disposal rate and Parkinson’s disease: cross-sectional and mortality analysis of NHANES 2003–2016 - Li, Xiaoting; Zeng, Zhaohao (Frontiers in Aging Neuroscience, 2025)
ObjectivesTo investigate the association between estimated glucose disposal rate (eGDR), a surrogate marker of insulin resistance, and Parkinson’s disease (PD) risk, and to examine the relationship between eGDR and all-cause mortality among PD patients.MethodsUsing data from the National Health and Nutrition Examination Survey (NHANES) 2003–2016, we conducted a cross-sectional study of 20,767 participants aged ≥40 years. eGDR was calculated using waist circumference, hypertension status, and HbA1c levels. PD cases were identified through anti-parkinsonian medication use. The association between eGDR and PD was examined using weighted logistic regression models with progressive adjustment for potential confounders. Survival analysis was performed in 255 PD patients to assess the relationship between eGDR and all-cause mortality.ResultsAmong participants, 256 had PD (weighted prevalence: 1.23%). Higher eGDR was associated with lower odds of PD in crude analysis (OR: 0.906, 95% CI: 0.856–0.960, P < 0.001). After full adjustment, the highest eGDR tertile showed significantly lower odds of PD compared to the lowest tertile (OR: 0.574, 95% CI: 0.337–0.976, P = 0.040). Restricted cubic spline analysis revealed a significant M-shaped non-linear relationship between eGDR and PD risk (P for non-linearity < 0.001). In survival analysis, higher eGDR was associated with lower mortality risk (adjusted HR: 0.875, 95% CI: 0.775–0.987, P = 0.030), with an inverted U-shaped relationship observed (P for non-linearity = 0.0352).ConclusionHigher eGDR levels are associated with lower PD risk and better survival in PD patients, suggesting that insulin sensitivity might play a role in PD pathogenesis and progression. These findings highlight the potential importance of metabolic health in PD.